RELIGIOUS LIFE FUNCTIONING ON A SYNODAL CHURCH THROUGH CONTRIBUTION THEIR CHARISM IN INDONESIA - Naibaho, Megawati; Sipahutar, Antonius P. (UNIKA Santo Thomas, 2024)
This study aims to investigate the Religious Life functioning on a synodal Church through contribution their charism. By and large, Indonesia is a country of multi religions. Yet, Religious Life as a specific Institute of life has a place in the society. A number of Religious Congregations consist of priests, sisters, and brothers have successfully persevered and maintained its existence in Indonesia society. The Vincentian Congregation’s which one among the Religious Congregations who play an important role functioning on a synodal Church of the local Church through its charism. The long-term presence of Vincentian Congregation particularly in Indonesia can be reflected through their history of the Congregation since its foundation in the Netherlands and expanded in Indonesia. The discussion on this paper is allocated only the KYM Congregation and CMM Brothers. Both congregations strive to realize charism through works of service. However, it must be acknowledged that the Congregations experience various challenges in living out the Congregation's spirituality and their charity. In order to gather data and explore the problem more deeply, this research uses a case study and a qualitative method through a literature study. The aim this paper to share the spirit of synodality inherit founders of the KYM and CMM Congregations. Hopefully, the two Congregations are able to continue the spirit of synodality that has been bequeathed by the founders. The KYM Sisters and CMM Brothers are called to work for the greater glory of God and the benefits of His people, especially the poor and the marginalized. Then, their primary task is to show their love to God through their charitable works for all people, especially the needy and the least brethren.